(untitled) (International Journal of Physiology, 2021)
Inherited color blindness is a lifelong challenge. While it may limit prospects for certain jobs, most people find ways to adapt to the condition. Colour vision defect is usually for red-green colour and it is X-linked recessive trait. It is mainly homozygous that develop colour vision defects. Female heterozygous usually have normal vision. Colour vision defects also have a strong genetic component , especially if both parents have colour vision defects , and people with a particular blood group , and very myopic or hypermetropic , there is a good chance their child will be same. Color blindness is often apparent at a young age when children are learning their colours and goes undetected because as they grow they learn to associate specific colours with certain objects.For example, they come to know that grass is green, so they call the colour they see green. If symptoms are very mild, a person may not realize that they don’t see certain colours.